Karakteristik Tradisi Islam Melayu Sebagai Representasi Islam Kultural - Salwa Aurumia Firanti; Meleza Andora; Maryamah; Zulhijra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Malay Islamic traditions are a form of religious expression that emerged from the interaction between Islamic teachings and the local culture of the Malay people. This study aims to analyze the characteristics of Malay Islamic traditions and examine their role as a representation of cultural Islam. The method used is library research, utilizing various sources of literature such as books, academic journals, and relevant previous research findings. Data analysis was conducted using a descriptive-qualitative approach through an examination of the concepts, values, and practices of Islamic traditions within Malay society.The research findings indicate that Malay Islamic traditions possess key characteristics, including the integration of adat (custom) and syariat (Islamic law), an emphasis on moral and social values, collective religious practices, and the use of cultural symbols that reflect the Islamic identity of the Malay community. Furthermore, this tradition demonstrates a harmonious process of acculturation between Islam and local culture without compromising the fundamental principles of Islamic teachings. Thus, Malay Islamic traditions can be understood as a representation of cultural Islam that presents an adaptive, moderate, and contextual face of Islam in community life.